Model Negara Menurut Perspektif Hizbut Tahrir Indonesia dan Syiah Imamiyah di Indonesia - Zamzamy, Ahmad (Global and Policy Journal of International Relations, 2015)
After the reform of 1998, the group Hizb ut-Tahrir Indonesia and the Shia Imami growing rapidly in Indonesia. Both groups have a controversy in Indonesian society. In addition to theological factors, both groups perceived to have an agenda to establish a state in Indonesia. This study also explores methods of how both groups realize his ideals. Hizb ut-Tahrir has idealism to replace the nation-state system and establish a caliphate and by means of non-violence. While the Shia Imami has idealistic state model Wilayatul faqih, but in the context of Indonesia, the Shia Imami has no agenda to establish a model of the country. There are fundamental differences between these two groups on the state model. Therefore there are different steps to realize these ideals. This study was conducted using qualitative descriptive data collecting literature and interviews with relevant parties.Kata-Kata Kunci: Hizbut Tahrir, Syiah Imamiyah, Model NegaraDOI:https://doi.org/10.33005/jgp.v3i02.1935